Anonna muricata Linn Leaf Effect in Inhibiting SGPT Elevation - Tanaya, Galih; Kuswinarti, Kuswinarti; Dewi, R. Nina Susana (Althea Medical Journal, 2015)
Background: Hepatitis is an infection or inflammation disease of the liver which is caused by virus, toxic substance, and immunological abnormalities. Soursop plant as a medicinal plants is known to have an antioxidant effect and nowadays is used as an alternative drug for hepatitis. One of the methods to assess liver function is to measure the serum Glutamate Piruvate Transaminase (SGPT) level. The purpose of this study was to find the effect of Soursop Leaf in inhibiting the SGPT elevation .Methods: An experimental study was conducted on 25 white male rats of wistar strain in the pharmacology laboratory of Faculty of Medicine, Universitas Padjadjaran during the period of September to October 2012. The rats were divided into 5 groups (group 1 and 2 as control; group 3, 4, and 5 as treatment groups treated by 200, 400, 600 mg/kgbw soursop extract, respectively). The soursop extract was administered to the treatment groups for 8 days. On the 8th day, group 2, 3, 4, and 5 received 1.6 ml CCl410% intraperitoneally. After 18 hours, the mean SGPT levels from all groups were measured. ANOVA test was used to analyze the result.Results : The mean SGPT levels were lower in the 3rd, 4th, and 5th group compared to group 2. There was a significant difference among treatment groups. Group 3 had the most significant result.Conclusion: Soursop leaf inhibits the elevation of SGPT level. Keywords: Hepatitis, SGPT, soursop leaf (Annona muricata) DOI: 10.15850/amj.v2n1.438